ΟΙ ΚΑΛΛΙΤΕΧΝΙΚΟΙ ΣΥΛΛΟΓΟΙ ΚΑΙ ΟΙ ΣΤΟΧΟΙ ΤΟΥΣ (1880-1910) - ΜΑΥΡΟΜΙΧΑΛΗ, ΕΥΘΥΜΙΑ Ε. (Μνήμων, 2001)
Efthimia Mavromichali, Artists associations in Greece 1880-1910 and their goals During the last twenty years of the 19th century and the first decadeof the 20th the first artists associations appear in Athens. Such societiesare founded mostly through the initiative of art-lovers and are indicativeof the new sociability of the rising middle classes of Athens. Artistsattempt to establish their own societies, to demarcate and safeguardtheir professional rights, but without success. Being, however, dependenton art-lovers for financial support and social power, artists are compelledto include them in their associations. The role of the artist in suchassociations is advisory and consultative. Thus artists associations inGreece differ from contemporary associations founded in the rest ofEurope, in that the principles governing their formation are not primarilybased on matters of style and artistic principles.In this study I examine the function and activity of three suchsocieties, namely, The Art-lovers' Society, The Artists' Union, and TheArtists' Society. The artistic activity during the period in question ismarked by the private initiatives of art-lovers and artists. This, however,stands in a wider social context that attributes a national andmoral mission to art and expects art to contribute to national renewal,especially after the devastating war of 1897.Artists' associations attempt to fulfil their mission in society bypromoting the fine arts, by cultivating the development of aestheticcriteria among a wide range of people and by supporting artists. Inpursuit of these goals, they organise exhibitions which, although notalways under strict artistic rules, give a significant impulse to art marketing,and pave the way for state initiatives in support of art and artists.